Jet Physics of Accreting Super-Massive Black Holes in the Era of the Fermi Gamma-ray Space Telescope - D'Ammando, Filippo (Frontiers in Astronomy and Space Sciences, 2017)
The Fermi Gamma-ray Space Telescope with its main instrument on-board, the Large Area Telescope (LAT), opened a new era in the study of high-energy emission from Active Galactic Nuclei (AGN). When combined with contemporaneous ground- and space-based observations, Fermi-LAT achieves its full capability to characterize the jet structure and the emission mechanisms at work in radio-loud AGN with different black hole mass and accretion rate, from flat spectrum radio quasars to narrow-line Seyfert 1 (NLSy1) galaxies. Here, I discuss important findings regarding the blazar population included in the third LAT catalog of AGN and the γ-ray emitting NLSy1. Moreover, the detection of blazars at redshift beyond three in γ rays allows us to constrain the growth and evolution of heavy black holes over cosmic time, suggesting that the radio-loud phase may be important for a fast black hole growth in the early Universe. Finally, results on extragalactic objects from the third catalog of hard LAT sources are presented.